Iliac Pseudoaneurysm, Only a Manifestation With More Causes: A Case Report. (August 2021) - Infante, Barbara; Di Lorenzo, Adelaide; Troise, Dario; Ferrante, Angela M. R.; Ruggieri, Maurizio; Stallone, Giovanni
Pseudoaneurysm is due to a disruption in arterial wall continuity. It forms a sac that communicates with the vessel lumen and is surrounded by the compressed, surrounding tissues and not by the wall of the artery from which the lesion arises. Many causes can predispose to the formation of a pseudoaneurysm such as trauma, surgical procedures, anticoagulation. In our patient another important risk factor for the formation of a pseudoaneurysm is ADPKD (autosomal dominant polycystic kidney disease) that can cause vascular complication. The mechanisms leading to the genesis of the pseudoaneurysms in our patient are unknown, but the clinicians should bear in mind when evaluating this type of patients that ADPKD may have a various range of systemic cardiovascular manifestation.